Deficits in latent inhibition induced by estradiol replacement are ameliorated by haloperidol treatment - Almey, Anne; Hafez, Nada; Hantson, Arne; Brake, Wayne G. (Frontiers in Behavioral Neuroscience, 2013)
There are sex differences in the symptomatology of schizophrenia, and in the response to antipsychotic treatments. One hallmark symptom of schizophrenia is a deficit in selective attention. Selective attention can be measured using a latent inhibition (LI) paradigm in humans; LI can be measured in rodents, and is used as an animal model of the selective attention deficits observed in schizophrenia. In the current experiments LI was used to clarify whether selective attention differs between male rats and ovariectomized (OVX) female rats receiving different estradiol (E2) replacement regimens. An additional aim was to determine whether haloperidol's facilitation of LI is enhanced by E2. Males and OVX female rats were trained in a conditioned emotional response LI paradigm. Females received no E2 replacement, a chronic low dose of E2 via silastic capsule, or a high phasic dose of E2 via silastic capsule accompanied by E2 (10 ug/kg SC) injections every fourth day. Actual plasma levels of E2 were determined using an enzyme linked immunosorbent assay. Rats were also administered a vehicle treatment, a 0.05mg/kg, or a 0.1mg/kg IP injection of haloperidol. Males and OVX females that did not receive E2 replacement both exhibited LI, but LI was not observed in the low and high E2 replacement groups. Haloperidol restored LI at a lower dose in the females receiving high E2 replacement compared to females receiving low E2 replacement, indicating that E2 replacement facilitates haloperidol in restoring LI.